Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine which expression correctly represents the determinant of the matrix [tex]\( A = \left[\begin{array}{ll}2 & 3 \\ 1 & 9\end{array}\right] \)[/tex], we will follow the formula for calculating the determinant of a 2x2 matrix.
For a general 2x2 matrix:
[tex]\[ A = \left[\begin{array}{ll}a & b \\ c & d\end{array}\right], \][/tex]
the determinant of [tex]\( A \)[/tex] is given by:
[tex]\[ \det(A) = ad - bc. \][/tex]
Applying this formula to our specific matrix:
[tex]\[ A = \left[\begin{array}{ll}2 & 3 \\ 1 & 9\end{array}\right], \][/tex]
we identify [tex]\( a = 2 \)[/tex], [tex]\( b = 3 \)[/tex], [tex]\( c = 1 \)[/tex], and [tex]\( d = 9 \)[/tex].
Plugging these values into the determinant formula, we get:
[tex]\[ \det(A) = (2)(9) - (1)(3). \][/tex]
Therefore, the correct expression for the determinant of [tex]\( A \)[/tex] is:
[tex]\[ \det(A) = (2)(9) - (1)(3). \][/tex]
Among the given options:
1. [tex]\(\operatorname{det}(A) = (2)(9) - (1)(3)\)[/tex]
2. [tex]\(\operatorname{det}(A) = (2)(9) + (1)(3)\)[/tex]
3. [tex]\(\operatorname{det}(A) = (2)(3) - (1)(9)\)[/tex]
4. [tex]\(\operatorname{det}(A) = (2)(3) + (1)(9)\)[/tex]
The first option, [tex]\(\operatorname{det}(A) = (2)(9) - (1)(3)\)[/tex], is the correct one.
For a general 2x2 matrix:
[tex]\[ A = \left[\begin{array}{ll}a & b \\ c & d\end{array}\right], \][/tex]
the determinant of [tex]\( A \)[/tex] is given by:
[tex]\[ \det(A) = ad - bc. \][/tex]
Applying this formula to our specific matrix:
[tex]\[ A = \left[\begin{array}{ll}2 & 3 \\ 1 & 9\end{array}\right], \][/tex]
we identify [tex]\( a = 2 \)[/tex], [tex]\( b = 3 \)[/tex], [tex]\( c = 1 \)[/tex], and [tex]\( d = 9 \)[/tex].
Plugging these values into the determinant formula, we get:
[tex]\[ \det(A) = (2)(9) - (1)(3). \][/tex]
Therefore, the correct expression for the determinant of [tex]\( A \)[/tex] is:
[tex]\[ \det(A) = (2)(9) - (1)(3). \][/tex]
Among the given options:
1. [tex]\(\operatorname{det}(A) = (2)(9) - (1)(3)\)[/tex]
2. [tex]\(\operatorname{det}(A) = (2)(9) + (1)(3)\)[/tex]
3. [tex]\(\operatorname{det}(A) = (2)(3) - (1)(9)\)[/tex]
4. [tex]\(\operatorname{det}(A) = (2)(3) + (1)(9)\)[/tex]
The first option, [tex]\(\operatorname{det}(A) = (2)(9) - (1)(3)\)[/tex], is the correct one.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.